In Vitro Exposure to the Endocrine-Disrupting Chemical Climbazole Impairs Human Sperm Motility, Hormonal Signalling, and Mitochondrial Activity - Eugenia Annunzi; Francesca Paola Luongo; Francesca Girolamo; Rosetta Ponchia; Sofia Passaponti; Paola Piomboni; Alice Luddi (Cells)
This study explores the endocrine-disrupting effects of climbazole (CBZ), an environmental and lifestyle stressor, on male fertility. The impact of CBZ on sperm vitality, motility, and molecular pathways related to hormone receptors and apoptosis was evaluated, in non-capacitated and capacitated conditions. Gene expression of key components, including hormone receptors (ESR1, ESR2, FSHR, AR), apoptosis-related genes (BAX, BCL2), and COX4l1 (involved in mitochondrial function), was analyzed. Protein tyrosine phosphorylation, a marker of capacitation, was also examined using immunofluorescence and Western blot analysis. We demonstrated that CBZ significantly reduced sperm vitality at concentrations above 25 µM and motility at 1 and 10 µM in non-capacitated and capacitated conditions. Changes in tyrosine phosphorylation patterns were also observed. Gene expression analysis revealed an upregulation of ESR1, ESR2, FSHR, and BAX, while AR and COX4l1 expression were downregulated. These findings offer new insights into the potential endocrine-disrupting and cytotoxic effects of CBZ, highlighting its potential role in compromising male reproductive health.